2019
DOI: 10.1128/jvi.01339-19
|View full text |Cite
|
Sign up to set email alerts
|

Related Enteric Viruses Have Different Requirements for Host Microbiota in Mice

Abstract: Accumulating evidence suggests that intestinal bacteria promote enteric virus infection in mice. For example, previous work demonstrated that antibiotic treatment of mice prior to oral infection with poliovirus reduced viral replication and pathogenesis. Here, we examined the effect of antibiotic treatment on infection with coxsackievirus B3 (CVB3), a picornavirus closely related to poliovirus. We treated mice with a mixture of five antibiotics to deplete host microbiota and examined CVB3 replication and patho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 32 publications
0
42
0
1
Order By: Relevance
“…Work performed in several labs has shown that antibiotic treatment reduces replication and pathogenesis of orally inoculated enteric viruses (6,(11)(12)(13)(14). However, the influence of antibiotics on systemic enteric virus infection is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Work performed in several labs has shown that antibiotic treatment reduces replication and pathogenesis of orally inoculated enteric viruses (6,(11)(12)(13)(14). However, the influence of antibiotics on systemic enteric virus infection is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a single dose of the aminoglycoside antibiotic streptomycin promoted the infiltration of neutrophils and inflammatory monocytes to the cecum (20). Interestingly, oral CVB3 infection is highly sensitive to antibiotics, where a single dose of streptomycin can significantly decrease viral replication and pathogenesis (6). Given that we and others have shown noncanonical effects of antibiotics, it is possible that systemic enteric virus infection could be influenced by antibiotic-induced innate immune response and/or immune cell infiltrates, although future experiments will be needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations